Learning about Sustainable Development Goals through English Language Teaching - Edita Bekteshi; Brikena Xhaferi (Research in Social Sciences and Technology, 2020)
The purpose of this paper is to introduce the concept of Sustainable Development (SD) and its goals to the students of the Faculty of Education, future teachers, in order to become skilled and knowledgeable and then introduce these Sustainable Development Goals (SDGs) to their students. As such, this study tries to link the concept of English Language Learning (ELL), English Language Teaching (ELT), and the SDGs as a type of all-inclusiveness within the “3 Ps”: Planet, People, and Profit. The instrument used for the purpose of this study was an online questionnaire sent to the students of the Faculty of Education in Kosovo. The total number of participants was 89. The students’ responses revealed that 60 percent of the future teachers are aware of the SD concept; however, the results indicate that not all “3 Ps” are hit upon by the future teachers. Based on the results, the most common areas of interest and societal needs of learning about SDGs are related to education, gender equality, good health and well-being, alleviation of poverty, and decent work and economics. These same goals are also hit upon in ELT classes. The study concludes that Kosovo’s future teachers are more concerned about issues related to social issues—“P-People”—followed by goals related to “P-Profit,” while goals related to “P-Planet,” the environment, are left behind. Future teachers’ knowledge about SDGs is vital, for there is a significant direct impact of learning about specific SDGs in higher education institutions, and the application of SDG topics in English language classes can infuse the SD concepts.